Estudo da estrutura porosa de empacotamento compacto aleatório de esferas rígidas. - Santana, David Wilson Oliveira (2017)
Around the 16th century, the study of the close packing of bodies had the simple function of optimizing physical space. The pioneer studies obtained great results at packing of bodies with simple geometries, provided the use of this study to model the nascent atomic structure. The studies were advanced to the point of being used to model complex structures, such as cell clusters and porous heterogeneous materials, being this last focus of this work. For this objective, we constructed random close packing of spheres hard frictionless, generated by computational algorithms commonly reported in the literature. Our studies characterized from a statistical point of view the porous medium formed by the empty regions of the random packing the spheres. Its statistical descriptors, the two-point statistical autocorrelation function ??2(??) and pore-size distribution were calculated and analyzed. Particular emphasis was given to the calculation of the entropy of the pore-size distribution and its interpretation in terms of the proximity of the system to the maximum density limit. Finally, we performed the reconstruction of the autocorrelation function calculated the natural rock the Lagoa-Salgada formation, based on statistical measurements performed on a random close packing of interpenetrable spheres. This last point is relevant in that the study showed that it is possible to reconstruct, even partially, the porous structure the natural porous material. In general, the results found in this work reproduced results presented in the literature about the morphological characterization of heterogenous media, as well as providing new ideas about the possibility of using statistical tools to reproduce the porous morphology observed in natural rocks.